Controlling metastatic cancer: the role of phytochemicals in cell signaling - Kapinova, Andrea; Kubatka, Peter; Liskova, Alena; Baranenko, Denis; Kruzliak, Peter; Matta, Milan; Büsselberg, Dietrich; Malicherova, Bibiana; Zulli, Anthony; Kwon, Taeg Kyu; Jezkova, Eva; Blahutova, Dana; et al. (Journal of cancer research and clinical oncology, 2019)
PURPOSE: Cancer is a serious health issue and a leading cause of death worldwide. Most of the cancer patients (approximately 90%) do not die from the consequences of the primary tumor development, but due to a heavily treatable metastatic invasion. During the lengthy multistep process of carcinogenesis, there are a lot of opportunities available to reverse or slow down the tissue invasion or the process of tumor metastasis formation. RESULTS: Current research has brought many promising results from anti-metastatic experimental studies, and has shown that chemoprevention by natural or semisynthetic phytochemicals with plethora of biological activities could be one of the potentially effective options in the fight against this problem. However, there is a lack of clinical trials to confirm these findings. In this review, we focused on summarization and discussion of the general features of metastatic cancer, and recent preclinical and clinical studies dealing with anti-metastatic potential of various plant-derived compounds. CONCLUSIONS: Based on our findings, we can conclude and confirm our hypothesis that phytochemicals with pleiotropic anticancer effects can be very useful in retarding and/or reversing the metastasis process, and can also be used to prevent tissue invasion and metastases. But, further studies in this area are certainly necessary and desirable.
Keywords: chemoprofylaxe; regulace genové exprese u nádorů; Animals; Drug Resistance, Neoplasm; metastázy nádorů; fytonutrienty; biologické markery; Biomarkers; invazivní růst nádoru; výsledek terapie; Epithelial-Mesenchymal Transition; Signaling pathways; Neoplasms; Gene Expression Regulation, Neoplastic; nádory; Metastatic cancer; fytogenní protinádorové látky; nádorové mikroprostředí; Chemoprevention; Therapy; lidé; staging nádorů; chemorezistence; signální transdukce; Treatment Outcome; klinická studie jako téma; Drug Evaluation, Preclinical; Antineoplastic Combined Chemotherapy Protocols; Signal Transduction; Clinical Studies as Topic; protokoly protinádorové kombinované chemoterapie; Antineoplastic Agents, Phytogenic; preklinické hodnocení léčiv; Tumor Microenvironment; epitelo-mezenchymální tranzice; Phytochemicals; zvířata; Neoplasm Invasiveness; Neoplasm Metastasis; Neoplasm Staging; Humans